Successful Treatment in a Child with Anaplastic Large Cell Lymphoma and Coexistence of Pulmonary Tuberculosis. (13th June 2013) - Baka, Margarita; Doganis, Dimitrios; Pourtsidis, Apostolos; Tsolia, Maria; Bouhoutsou, Despina; Varvoutsi, Maria; Strantzia, Katerina; Kosmidis, Helen
Abstract : A 13-year-old girl was admitted to our department with a history of severe pain of her left axilla and fever. On physical examination, a block of lymph nodes in her left axilla, diffuse papular rash, and red-violet swelling of her supraclavicular and subclavian region were noted. Imaging investigations revealed left axillar and supraclavicular lymphadenopathy and a small nodular shade in the upper lobe of her left lung. A biopsy from an axillary lymph node established the diagnosis of anaplastic large cell lymphoma (ALCL), whereas DNA of Mycobacterium tuberculosis was detected by polymerase chain reaction (PCR) in the same tissue biopsy. Patient was started on chemotherapy for ALCL and achieved remission of all initially involved fields. Nevertheless, two new nodular lesions were detected in the left lower lobe. Biopsy revealed granulomas, and PCR was positive for M. tuberculosis . Our patient received treatment with the combination of isoniazid and rifampin (12 months), pyrazinamide (the first 2 months), and maintenance chemotherapy for her ALCL for one year simultaneously. Four years later, she is disease free for both mycobacterial infection and lymphoma. We are reporting this successful management of mycobacterial infection in a patient with ALCL despite intensive chemotherapy that the patient received at the same time.